1997
DOI: 10.1021/je970060t
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagrams of Aliphatic Alcohols + Magnesium Sulfate + Water

Abstract: Phase diagrams for aliphatic alcohols + magnesium sulfate + water were measured. The alcohols used were ethanol, 1-propanol, 2-propanol, and 2-methyl-2-propanol. Phase diagram data were obtained at 25 °C, and for magnesium sulfate + ethanol + water at 25 °C and 35 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…They found that the presence of 1-propanol significantly reduced the solubility of the aqueous solution of potassium sulfate. Zafarani-Moattar et al , studied the ethanol or 1-propanol or 2-propanol or 2-methyl-2-propanol + Mg 2 SO 4 or (NH 4 ) 2 HPO 4 or NH 4 H 2 PO 4 + water systems at 25 °C and 35 °C. Wang et al studied 1-propanol or 2-propanol + water + KF systems.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the presence of 1-propanol significantly reduced the solubility of the aqueous solution of potassium sulfate. Zafarani-Moattar et al , studied the ethanol or 1-propanol or 2-propanol or 2-methyl-2-propanol + Mg 2 SO 4 or (NH 4 ) 2 HPO 4 or NH 4 H 2 PO 4 + water systems at 25 °C and 35 °C. Wang et al studied 1-propanol or 2-propanol + water + KF systems.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of 1‐propanol as a function of salt concentration for the four salts tested, and for the published salts CsCl, KF, Na 2 SO 3 , disodium hydrogen citrate(Na 2 C 6 H 6 O 7 ), MgSO 4 , dipotassium Oxalate(C 2 K 2 O 4 ), Na 2 S 2 O 3 , ZnSO 4 , LiCl, NaBr, NaCl, KCl, MnSO 4 were analyzed by fitting Eqn (3) to obtain k s values . The results were shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The precipitation reaction of MgSO 4 was closely related to the solubility of the MgSO 4 in the ethanol-water-MgSO 4 system. Zafarani-Moattar and Salabat measured the solubility of MgSO 4 in a mixed solution of water and ethanol at 25°C [31]. As the portion of the ethanol increased in the mixture of water and ethanol, the solubility of the MgSO 4 decreased.…”
Section: Precipitation Of Mgsomentioning
confidence: 99%